Uswah Hasanah as a Methodology of Islamic Education - Ruswandi, Agus; Junaedi, Dedi; Rahmatullah, Ari Abdul Kohar (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract The purpose of the Prophet Muhammad was sent was to perfect human morality and the Prophet Muhammad PBUH as an example or role model who could be a role model for Muslims. The role model in the context of the verses of the Qur’an is called Uswah Hasanah. The success of the Prophet Muhammad in preaching was due to having uswatun hasanah in carrying out da’wah in which there were educational values both in terms of substance, approach and methodology. In the Qur’an the term Uswatun Hasanah is shown to the Prophet Ibrahim as and Prophet Muhammad PBUH. Uswatun hasanah of the prophets is a noble behavior that is an example for other humans. Uswatun hasanah includes being exemplary in morals, being patient in preaching, and being steadfast in facing tests. In the context of education, All parties involved in the educational process must be able to be role models for others. The success of the education and preaching of the Prophet Muhammad PBUH was because the prophet could be an example, an example, could be followed, and became a role model for others.Abstrak Tujuan Nabi Muhammad diutus adalah untuk menyempurnakan akhlah manusia dan Nabi Muhammad PBUH sebagai contoh atau suri tauladan yang bisa menjadi role model bagi umat Islam. Suri tauladan dalam konteks ayat Al-Qur’an disebut Uswah Hasanah. Kesuksesan Nabi Muhammad PBUH dalam berdakwah adalah karena memiliki uswatun hasanah dalam melakukan dakwah yang di dalamnya terdapat nilai-nilai pendidikan baik dari sisi subtansi, pendekatan maupun metodologis. Dalam Al-Qur’an istilah Uswatun Hasanah ditunjukkan kepada Nabi Ibrahim a.s dan Nabi Muhammad PBUH. Uswatun hasanah para nabi merupakan perilaku yang mulia yang menjadi teladan bagi manusia lainnya. Uswatun hasanah meliputi teladan dalam akhlak, sabar dalam berdakwah, dan tabah menghadapi ujian. Dalam konteks pendidikan, semua pihak yang terlibat dalam proses pendidikan harus dapat menjadi teladan bagi yang lain. Kesuksesan pendidikan dan dakwah Nabi Muhammad PBUH adalah karena nabi dapat menjadi teladan, contoh, bisa diikuti, dan jadi panutan bagi yang lainnya.